The Influence of Price and Product Quality on Customer Satisfaction of The Body Shop Among Generation Z in Bandar Lampung - Putri, Safira Nandita; Soegoesti, Dwi Gema; Ahadis, Hamartoni; Candra, Ade (Universitas Muhammadiyah Pontianak, 2026)
This study examines how price perception and product quality affect Generation Z consumer satisfaction with The Body Shop in Bandar Lampung. Using a quantitative explanatory survey with purposive sampling, data were collected from 100 Gen Z respondents and analyzed using multiple linear regression. Results show that price perception negatively impacts satisfaction, while product quality has a positive and more dominant effect. Both variables significantly influence satisfaction. The findings suggest that The Body Shop should focus on maintaining product quality, particularly sustainability and ethical values, while implementing competitive pricing strategies to enhance Gen Z satisfaction and loyalty.